Efektifitas Senam Dengan Modul Dalam Mengurangi Dismenore Pada Remaja SMA Di Kota Surakarta - Yuyun Setyorini; Satino Satino (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Dysmenorrhea, Adolescents, Reproductive Health Module. Dysmenorrhea is the most common gynecological problems experienced by women. Based on the research background mentioned above, can be formulated research question "Are gymnastics with reproductive health module is effective in reducing dysmenorrhea in adolescents with dysmenorrhea in Surakarta?". While the purpose of the study was to determine the effectiveness of the exercise with the reproductive health module in reducing dysmenorrhea in adolescent high school in Surakarta. This research is quantitative research with quasi-experimental designs and designs were used pretest-posttest design. In the design of this group of teenagers is trained gymnastics dysmenorrhea with the use of reproductive health module. Where the research is in the area of Surakarta. While the research time from March to August 2015. In this study, using the chi-square test. The results showed p-value = 0.000 (p <0.05), which means that there is a significant effect on pain intensity between before and had performed the action. Advice for health workers to provide health education on reproductive health for young women as early as possible and further research to investigate specifically related to reproductive health in adolescents.